Adolescents' Conformity to the Television Viewing Behaviour of their Classmates: A Longitudinal Study. (November 2016) - Beyens, Ine; Vandenbosch, Laura; Bekalu, Mesfin Awoke; Eggermont, Steven
While it is well understood that demographic, cultural, and personality characteristics predict adolescents' television viewing, little is known about adolescents' conformity to the television viewing behaviour of their peers. In particular, there is a lack of research that investigates the similarity in television programme preferences among adolescents and their classmates. The current three-wave panel study involving 732 adolescents showed that, at baseline, adolescents watched one-fourth of the television programmes that their classmates watched. Adolescents were more likely to conform to the television programme preferences of their classmates than to the preferences of non-classmates. Latent growth curve modelling demonstrated that the similarity in programme preferences among adolescents and their classmates increased over time. Adolescents' overall television viewing predicted the baseline similarity in programme preferences and adolescents' degree of social viewing, access to a bedroom television, and the total amount of television viewing predicted the long-term growth in similarity.